2022
DOI: 10.7759/cureus.29504
|View full text |Cite
|
Sign up to set email alerts
|

The Stigmatizing Attitudes of Syrian University Students Toward Schizophrenia

Abstract: Background: Stigma is frequently considered an obstacle to schizophrenia treatment and recovery. However, little is known regarding the stigma experienced by persons with schizophrenia among Syrian college students.Methods: A total of 963 students from Syrian colleges and universities participated in this study, using a questionnaire with a case vignette illustrating schizophrenia. The questionnaire inquired about people's attitudes toward schizophrenia and their desire to avoid contact with people with schizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…The ndings were consistent with previous reports that people with schizophrenia faced a higher level of stigma than people with other mental illnesses. [35], [36] The results indicated that the patterns of personal stigma and perceived stigma varied between schizophrenia, depression, and GAD. The beliefs that people with the problem are dangerous and unpredictable were signi cantly higher for the schizophrenia vignette and much higher than in other studies about stigma among university students [35], [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ndings were consistent with previous reports that people with schizophrenia faced a higher level of stigma than people with other mental illnesses. [35], [36] The results indicated that the patterns of personal stigma and perceived stigma varied between schizophrenia, depression, and GAD. The beliefs that people with the problem are dangerous and unpredictable were signi cantly higher for the schizophrenia vignette and much higher than in other studies about stigma among university students [35], [37].…”
Section: Discussionmentioning
confidence: 99%
“…[35], [36] The results indicated that the patterns of personal stigma and perceived stigma varied between schizophrenia, depression, and GAD. The beliefs that people with the problem are dangerous and unpredictable were signi cantly higher for the schizophrenia vignette and much higher than in other studies about stigma among university students [35], [37]. With the development of internet media in recent years, media reports about violence related to schizophrenia may have contributed to the perception of dangerousness.…”
Section: Discussionmentioning
confidence: 99%